Diseño de oferta gastronómica gourmet que contribuya al mejoramiento de la comida típica en el cantón Bolívar, provincia de Manabí. - Zambrano Mendoza, Henry Javier (2014)
This thesis, gourmet cuisine design that contributes to the improvement of the typical food in Canton Bolívar province of Manabi, the principal object of study reviewing several documents of national and foreign literature related manuals and cookbooks gourmet. Its overall objective has been to design a gourmet offering typical food manabita to contribute and strengthen the supply of food tourism in the canton Bolivar, also specific well objectives: to systematize theoretical precepts relating to domestic and foreign bibliography regarding the offer gourmet systematically review the methodological procedures for the design of the gourmet offering typical food manabita in rural counties and develop a standard typical food recipes manabita focused on gourmet offering for culinary tourism development in the canton Bolívar. Through research techniques such as interviews, surveys and applying the SWOT matrix, problem identification study allowed. In conclusion it is found that implementing the elemental design of a typical offering gourmet food manabita for culinary tourism development in Canton Bolívar